Enhancing Students’ Numeracy Literacy through ASICC-SSI Worksheets in Environmental Change Learning - Silvia Okki Novita Rinda; Priyatmoko; Akhmad Sukri; Siti Ramdiah; Nurul Bahiyah Abd Wahid; Agus Muji Santoso; Poppy Rahmatika Primandiri (UNIVERSITAS PGRI MADIUN, 2026)
Developing students’ numeracy literacy is an important goal in science education, particularly for understanding environmental phenomena that require data interpretation and quantitative reasoning. However, classroom learning often provides limited opportunities for students to analyze environmental issues using scientific evidence and numerical information. This study aimed to develop ASICC-based student worksheets integrating Socio-Scientific Issues (SSI) on environmental change topics to strengthen students’ numeracy literacy. The study employed design research using a development study approach based on Tessmer’s formative evaluation model, consisting of preliminary study and formative evaluation stages, including self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field testing. The participants were 36 tenth-grade students at SMA Negeri 1 Prambon. Data were collected through observations, interviews, and expert validation sheets and analyzed using descriptive quantitative methods. The validation results indicated that the developed worksheets were categorized as valid to very valid, with scores of 73%, 98%, and 93% from experts and practitioners. Learning activities structured through the ASICC stages encouraged students to analyze environmental issues, interpret data, and formulate evidence-based solutions. These findings suggest that ASICC-based worksheets integrated with SSI have the potential to strengthen students’ numeracy literacy in environmental change learning.